2008
DOI: 10.1111/j.1600-051x.2008.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor polymorphism (−1056 Taq‐I) interacts with smoking for the presence and progression of periodontitis

Abstract: Vitamin D receptor Taq-I TT polymorphism was moderately associated with both the presence and the progression of periodontitis in smokers, while no association was detected in non-smoking individuals. VDR genetic factors may interact with smoking in the pathogenesis of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
1
35
2
1
Order By: Relevance
“…In particular, the TT genotype and the presence of T allele are associated with chronic periodontal disease in Japanese, Chinese and Caucasian subjects (23)(24)(25)(26)(27). This data is also in accordance with our previous study which showed a strong correlation between TT genotype of Italian subjects and chronic periodontitis (OR 3.59) but also with aggressive periodontal disease (28).…”
Section: Taqisupporting
confidence: 81%
“…In particular, the TT genotype and the presence of T allele are associated with chronic periodontal disease in Japanese, Chinese and Caucasian subjects (23)(24)(25)(26)(27). This data is also in accordance with our previous study which showed a strong correlation between TT genotype of Italian subjects and chronic periodontitis (OR 3.59) but also with aggressive periodontal disease (28).…”
Section: Taqisupporting
confidence: 81%
“…In a recent longitudinal study, Nibali et al [32] found a moderate association between VDR Taq-I polymorphism and periodontitis presence/progression in smokers but no association in non-smokers, concluding that VDR genetic factors may interact with smoking in the pathogenesis of periodontitis [32]. In our study, the association of different BsmL haplotypes was not significant when the analysis controlled for tobacco consumption, age, and number of teeth present.…”
Section: Discussioncontrasting
confidence: 45%
“…Several studies have revealed the presence of particular VDR gene allelic forms which influence the frequency of periodontitis. TaqI polymorphism in VDR gene, particularly the of TT genotype, was associated with an increased risk of chronic periodontitis (CP) as reported by Tachi et al (2003), Wang et al (2009), Brett et al (2005), Nibali et al (2008 and Martelli et al (2011) while Toniato Borges et al (2009 observed a higher incidence of CP in patients with Tt genotype. Sun et al (2002) suggested the involvement of Tt genotype in the development of early-onset periodontitis.…”
Section: Periodontitismentioning
confidence: 71%